Transcriptional regulator NtrC modulates nitrogen assimilation, virulence, and the extracellular glutamine synthetase activity in Acinetobacter baumannii - Akram J. Alahmar; Noha M. Elhosseiny; Rehab R. Mahmoud; Ahmed S. Attia (PLoS ONE, 2026)
Acinetobacter baumannii is a growing threat characterized by worrisome antibiotic resistance. A deeper understanding of its resistance and virulence mechanisms is essential for developing new and effective treatments. Herein, we explore the role of the two-component (NtrB-NtrC) signal transduction system and two distinct glutamine synthetases (GlnA-1 and GlnA-2) in the nitrogen assimilation, stress response, and virulence in A. baumannii . Under nitrogen-limited conditions, the ntrC mutant showed significantly defective growth kinetics when ammonium was the sole source of nitrogen, whereas the glnA2 mutant exhibited an obvious growth defect when putrescine was the sole source of nitrogen. Moreover, under nitrogen limitation, the glnA1 and glnA2 expression increased by approximately twofold and ninefold, respectively. An enzymatic activity assay demonstrated that the A. baumannii extracellular glutamine synthetase activity is dependent on the type II secretion system (T2SS), confirming our previous results from a T2SS secretome study. Interestingly, this activity is also regulated by NtrC. An infection model using Galleria mellonella revealed that the ntrC mutant was significantly less virulent than both the wild-type and glnA2 mutant strains. These results provide new insights into the nitrogen regulatory network and its contribution to the A. baumannii virulence, underscoring NtrC as a promising target for future antimicrobial strategies.